Molecular Identification, Histopathology and Antibiotic Susceptibility Profiling of Aeromonas veronii Isolated from Oreochromis niloticus in Bangladesh - Sayed Mashequl Bari; Mohammad Muttakinul Islam; Aktia Amina; Marufa Khatun; A. M. Shahabuddin (Veterinary Medicine and Science)
ABSTRACT Background Tilapia (Oreochromis niloticus) is the most widely cultured freshwater fish species in Bangladesh and worldwide. However, commercial tilapia culture systems face increasing challenges from bacterial infections. Objectives The objective of this study was to identify the bacterial isolates from infected tilapia in an intensive cage culture farm located along the Shitalakshya River in Bangladesh. Methods Infected fish samples were collected and underwent comprehensive clinical and post‐mortem investigations, followed by phenotypic, biochemical and molecular identification of the bacterial isolates, as well as histopathological and antibiotic susceptibility examinations. Results Phenotypic and biochemical characterization showed similarities of the ‐collected isolates with Aeromonas veronii. Moreover, molecular analysis of the bacterial conserved region 16S rRNA also confirmed these isolates as A. veronii. The analysed 16S rRNA sequence (GenBank accession no. PP832815) showed a close relationship (100% identity) with A. veronii from China (GenBank accession no. MT071624) in the NCBI BLAST search, and in the phylogenetic tree, they grouped in a single clade. This close genetic relationship is also supported by the low genetic distance between the isolates. Histopathological analysis revealed gross pathological changes like necrosis, hypertrophy and inflammation in muscle tissues. The isolates were found to be sensitive to multiple antibiotics but resistant to trimethoprim and sulphamethoxazole. Conclusion This study investigated the presence of A. veronii infection in tilapia (O. niloticus) in an intensive cage culture farm in Bangladesh.